Behavioral performance and visual strategies during skill acquisition using a novel tool use motor learning task - T. J. Bosch (Nature Portfolio, 2018)
Abstract Habitual tool use is considered a hallmark of human evolution. One potential explanation for humanity’s advanced tool using abilities is that humans possess a unique neurobiological system that estimates efficient ways to manipulate objects with novel tools, resulting in rapid tool use motor learning. However, since humans regularly use a multitude of tools, examining these underlying processes is challenging. As such, we developed a tool use motor learning paradigm that utilizes a challenging tool (chopsticks) in order to accomplish a difficult behavioral task that requires extensive practice to continuously improve one’s proficiency. We then assessed the paradigm by recruiting participants with little experience using chopsticks and training them over the course of eight training sessions to grasp marbles with chopsticks and drop them in a cylindrical container. Throughout training, we examined behavioral performance and visual strategies to determine whether practicing the task resulted in outcomes congruent with traditional motor learning. Results show that performance increases in a logarithmic pattern and is accompanied by decreased confirmatory visual strategies. Since these findings are congruent with those seen in traditional motor learning, this paradigm is a novel method for use in future research examining the underlying mechanisms that mediate tool use motor learning.